Silicate fluorescent powder with apatite structure, preparation method of silicate fluorescent powder and application of silicate fluorescent powder in field of optical temperature sensing

By doping Bi3+ and Eu3+ in the apatite structural silicate phosphor, high temperature sensitivity and excellent luminous performance in the field of optical temperature sensing are achieved, and the problem of poor temperature sensitivity of traditional phosphors is solved.

CN119570487AActive Publication Date: 2025-03-07JILIN UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411747079.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-03-07
Estimated Expiration
2044-12-02

AI Technical Summary

Technical Problem

Existing optical thermometers have limitations in measuring objects in mobile or corrosive environments, and traditional phosphors have poor temperature sensitivity in the field of optical temperature sensing.

Method used

Apatite structure silicate phosphor is used, with the chemical formula Mg2Gdz(SiO4)6O2:0.01Bi3+, xEu3+, where 0

Benefits of technology

The high temperature sensitivity and excellent luminescence performance of the phosphor in the field of optical temperature sensing are achieved, with a maximum relative sensitivity of 0.92% K-1, which is higher than the temperature-sensitive phosphor results reported in related literature.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119570487A_ABST
    Figure CN119570487A_ABST
Patent Text Reader

Abstract

The invention provides silicate fluorescent powder with an apatite structure, a preparation method of the silicate fluorescent powder and application of the silicate fluorescent powder in the field of optical temperature sensing, and relates to the technical field of fluorescent materials. The chemical formula of the fluorescent powder is Mg2Gdz (SiO4) 6O2: 0.01 Bi < 3 + >, xEu < 3 + >, 0 lt; x is less than or equal to 0.12, and z is 8 (1-0.01-x). In a Mg2Gd8 (SiO4) 6O2 matrix, Bi < 3 + >-Eu < 3 + > energy transfer is adjusted by controlling the doping concentration of Eu < 3 + >, and tuning of the fluorescent powder from blue light to red light is achieved; especially, energy transfer from Bi < 3 + > to Eu < 3 + > in the heating and cooling process is beneficial for improving the temperature measurement sensitivity of the FIR-based fluorescent temperature probe, and high-sensitivity optical temperature sensing (the maximum relative sensitivity reaches 0.92% K <-1 > (498K)) is realized. Meanwhile, the fluorescent powder can also be widely applied to the field of temperature visualization.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of fluorescent materials, and in particular to an apatite structure silicate fluorescent powder and a preparation method thereof and an application thereof in the field of optical temperature sensing. Background Art

[0002] At present, environmental protection and energy conservation and emission reduction are global challenges. According to statistics, the global electricity consumption in the field of lighting accounts for about 20% of the total electricity consumption, and most of the electrical energy cannot be converted into light energy, but is released as heat and other forms of energy. Activator ion-doped photoluminescent phosphors are widely used in the field of solid-state lighting due to their good stability, high luminous efficiency, energy saving and environmental protection. With the in-depth study of phosphors, it is found that the application of phosphors is no longer limited to the field of solid-state lighting, and multifunctional applications are also being developed in other fields, one of which is optical temperature measurement.

[0003] Traditional contact thermometers have many limitations during use, such as being unable to measure moving objects, unable to measure objects in corrosive environments, and unable to test smaller objects. In contrast, non-contact optical thermometers have the advantages of wide measurement range, fast response, and high resolution without the need for direct contact with the object being measured, and can meet the requirements of fast and accurate measurement. For optical thermometers, the principle is mainly based on temperature-related optical parameters, such as the fluorescence intensity ratio (FIR), spectral shift, luminescence lifetime, emission bandwidth, and luminescence intensity, etc., which change with temperature.

[0004] Apatite structure crystals have (A1) 2 (A2) 3 (XO 4 ) 3 The general chemical formula of Y, wherein A1 and A2 represent divalent alkaline earth metal ions Ca 2+ , Sr 2+ , Ba 2+ etc., Y is mainly F - , Cl - OH - , XO 4 Indicates PO 4 3- 、SiO 4 4- , VO 4 3- In recent years, apatite structure phosphors have been reported frequently. Apatite, as an important phosphor matrix material, gives apatite structure phosphors high efficiency, thermal stability and chemical stability. Among them, most of the rare earth apatite structure phosphors have P6 3 / m space group with high symmetry. As the cations in the crystal are replaced by other ions, the apatite structure crystal changes from P6 3 / m high symmetry space group becomes relatively low symmetry P6, P63, P3 and P2 1 / m space group. In recent years, researchers have turned their attention to main group metal ions (Bi 3+ , Pb 2+ Sn 4+ ) and transition metal ions (Cr 3+ 、Co 3+ , Mn 2+ , Mn 4+ ) and other non-rare earth ions. Compared with precious and scarce rare earth resources, bismuth ions have many advantages, such as large mineral resource reserves and relatively simple purification process, and have good prospects in many fields such as luminescence.

[0005] Bismuth (Bi 3+ ) and narrow-band characteristic emission of trivalent rare earth ions (Re 3+ ) are considered to be the best combination for optical temperature measurement due to their completely different electronic structures and temperature responses. 3+ Ion Ce 3+ 、Eu 3 + Like the 4fn electron configuration, Re has broadband emission, and its luminescence performance is easily affected by environmental factors. Under certain excitation, it exhibits multiple emission bands, covering the range from ultraviolet light to red light. 3+ The emission spectra of the ions are all characteristic narrow-band emission, the peak shape and position of the emission peak are not easily affected by the crystal field environment, and the luminescence lifetime is also long. This combination is considered to be a strong candidate material in the fields of optical thermometers and optical anti-counterfeiting. 2 O 6 :Bi 3+ / Ln 3+ (Ln=Eu / Sm / Dy / Tb) series phosphors, Ca 3 Sc 2 Si 3 O 12 :Bi 3+ / Tb 3+ / Eu 3+ Phosphor, LaScO 3 :Bi 3+ / Tb 3+ / Eu 3+ Phosphors, etc. Although these reported phosphors all have temperature measurement performance, they generally have the problem of poor temperature sensitivity. Summary of the invention

[0006] In view of this, the object of the present invention is to provide an apatite structure silicate phosphor and a preparation method thereof and application in the field of optical temperature sensing. The apatite structure silicate phosphor provided by the present invention has excellent luminescence performance and temperature sensitivity.

[0007] The present invention provides an apatite structure silicate phosphor, the chemical formula of which is: Mg 2 G z (SiO 4 ) 6 O 2 :0.01Bi 3 + ,xEu 3+ ; where 0 <x≤0.12,z=8(1-0.01-x)。

[0008] Preferably, x is 0.0025, 0.005, 0.01, 0.02, 0.04, 0.08 or 0.12.

[0009] The present invention provides a method for preparing the apatite structure silicate phosphor described in the above technical solution, comprising the following steps:

[0010] Mixing a magnesium source, a gadolinium source, a silicon source, a bismuth source and a europium source according to the stoichiometric ratio shown in the chemical formula of the apatite structure silicate phosphor to obtain a mixture;

[0011] The mixed material is calcined in an air atmosphere and then ground to obtain the apatite structure silicate phosphor.

[0012] Preferably, the magnesium source includes one or more of magnesium oxide, magnesium nitrate, magnesium hydroxide and magnesium carbonate; the gadolinium source includes one or more of gadolinium oxide, gadolinium nitrate and gadolinium fluoride; the silicon source includes silicon dioxide; the bismuth source includes one or more of bismuth oxide, bismuth nitrate, bismuth hydroxide and bismuth carbonate; the europium source includes one or more of europium oxide, europium nitrate, europium hydroxide and europium carbonate.

[0013] Preferably, the mixing method is grinding.

[0014] Preferably, the grinding is performed with the addition of a grinding medium, and the grinding medium is ethanol.

[0015] Preferably, the calcination temperature is 1300-1500° C. and the calcination time is 4-6 hours.

[0016] Preferably, the calcination temperature is 1450° C. and the calcination time is 5 hours.

[0017] The present invention provides the application of the apatite-structured silicate phosphor described in the above technical solution or the apatite-structured silicate phosphor prepared by the preparation method described in the above technical solution in the fields of solid-state lighting, optical temperature sensing, and temperature visualization.

[0018] Preferably, the optical temperature sensing includes a non-contact optical temperature measurement device.

[0019] The present invention provides an apatite-structured silicate phosphor with the chemical formula: Mg 2 Gd z (SiO 4 ) 6 O 2 :0.01Bi 3 + ,xEu 3+ ; where 0 < x ≤ 0.12 and z = 8(1 - 0.01 - x). The phosphor provided by the present invention is a bismuth- and europium-codoped activated silicate luminescent phosphor with Mg 2 Gd 8 (SiO 4 ) 6 O 2 (abbreviated as MGSO) as the original matrix material. The present invention uses a specific matrix material, doping Eu 3+ into MGSO:Bi 3+ , studying the energy transfer mechanism of Bi 3+ → Eu 3+ in MGS:Bi 3+ ,Eu 3+ , and realizing the tuning of the phosphor from blue light to red light by controlling the doping concentration of Eu 3+ ; moreover, the emission spectrum of MGSO:Bi 3+ is relatively sensitive to temperature changes, and the narrow-band emission of Eu 3 + is insensitive to temperature changes. Based on the fluorescence intensity ratio (FIR) of MGSO:Bi 3+ and Eu 3+ changing with temperature, high sensitivity of the phosphor to temperature can be achieved. According to the FIR of MGS:Bi 3+ ,Eu 3+ changing with temperature, this phosphor is applied to non-contact optical temperature measurement. The phosphor provided by the present invention can be effectively excited by ultraviolet light and near-ultraviolet light in the range of 250 - 450 nm, has a wide absorption range, high emission intensity, and excellent color stability, and is a light conversion material with good luminescence characteristics and stability; and has excellent temperature sensitivity and FIR recovery during the heating and cooling processes.

[0020] The results of the examples show that the apatite-structured silicate phosphor provided by the present invention, with the increase of Eu3+ With the increase of co-doping concentration, the luminescent color can transition from the blue light region to the red light region, thus realizing the spectrum regulation of the phosphor; the variable temperature spectrum shows that Bi 3+ The broadband emission peak ratio of Eu 3+ The narrowband emission peak intensity is more sensitive to temperature changes. Based on this feature, a novel MGSO:0.01Bi 3+ ,0.01Eu 3+ The temperature-sensitive response relationship of the fluorescence intensity ratio of the phosphor at different temperatures was calculated, and the relative sensitivity (S r ), maximum relative sensitivity S r =0.92%K -1 , which is higher than the results of temperature-sensitive phosphors reported in relevant literature.

[0021] The present invention provides a method for preparing the apatite structure silicate phosphor described in the above technical solution, which has abundant raw material sources, low prices, simple preparation process, low equipment requirements and low production costs.

[0022] The present invention provides the application of the apatite structure silicate phosphor described in the above technical solution or the apatite structure silicate phosphor prepared by the preparation method described in the above technical solution in an optical temperature sensor. The apatite structure silicate phosphor provided by the present invention can be excited by ultraviolet to blue light in the range of 250 to 450 nm, and emits a spectrum tuned from blue to red in the range of 350 to 750 nm. The main emission peak is located in the blue light region of 446 nm and the orange light region of 613 nm. It has good matching with the output wavelength of near-ultraviolet LED chips (355 to 365 nm, 380 to 410 nm) and blue LED chips (445 to 455 nm), and can be used in the field of white light LEDs; the phosphor has excellent temperature sensitivity and can be used in the field of temperature sensing, such as non-contact optical temperature measurement and visualization. The phosphor provided by the present invention has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a photo of the phosphor obtained in Examples 2 to 7 under a 365nm UV lamp. Figure 1 From left to right in the figure, they correspond to the phosphors of Example 2, Example 3, Example 4, Example 5, Example 6, and Example 7;

[0024] Figure 2 These are luminescent photos of the phosphors obtained in Examples 8 to 14 under a 365nm UV lamp. Figure 2 From left to right in the figure, they correspond to the phosphors of Example 8, Example 9, Example 10, Example 11, Example 12, Example 13, and Example 14;

[0025] Figure 3PL spectra of the phosphors obtained in Examples 8 to 14 under 315 nm excitation;

[0026] Figure 4 MGSO:1mol%Bi 3+ ,ymol%Eu 3+ (y=0.25~12.00) CIE chromaticity coordinates of the sample, Figure 4 (a) is the CIE chromaticity coordinate diagram, (b) is the chromaticity coordinate value of the phosphor at room temperature when y=0.25~12.00;

[0027] Figure 5 MGSO: 1 mol% Bi in the example 3+ MGSO:1mol%Bi 3+ ,1mol%Eu 3+ and XRD diffraction pattern of MGSO;

[0028] Figure 6 MGSO: 1 mol% Bi in the example 3+ ,1mol%Eu 3+ Rietveld refined XRD spectrum of phosphor;

[0029] Figure 7 MGSO prepared in Example 10: 1 mol% Bi 3+ ,1mol%Eu 3+ SEM image and elemental mapping distribution (EDS) image of phosphor;

[0030] Figure 8 Schematic diagram of the crystal structure of MGSO;

[0031] Fig. 9 MGSO: 1 mol% Bi in the example 3+ ,1mol%Eu 3+ Temperature-dependent PL spectra of;

[0032] Fig.10 for Bi 3+ and Eu 3+ The trend diagram of the integrated intensity changing with temperature;

[0033] Fig.11 is the temperature-dependent FIR fitting curve;

[0034] Fig.12 MGSO:1mol%Bi 3+ ,1mol%Eu 3+ The variation of Sa and Sr values ​​of phosphor with temperature;

[0035] Fig.13MGSO:1mol%Bi 3+ ,1mol%Eu 3+ FIR recovery of phosphor during heating and cooling process;

[0036] Fig.14 MGSO:1mol%Bi 3+ ,1mol%Eu 3+ The CIE chromaticity coordinates of the phosphor in the temperature range of 298 to 498K, Fig.14 (a) is the CIE chromaticity coordinate diagram, (b) is MGSO: 1mol%Bi 3+ ,1mol%Eu 3+ The chromaticity coordinate value of the phosphor in the temperature range of 298~498K. DETAILED DESCRIPTION

[0037] The present invention provides an apatite structure silicate phosphor, the chemical formula of which is: Mg 2 G z (SiO 4 ) 6 O 2 :0.01Bi 3 + ,xEu 3+ ; where 0 <x≤0.12,z=8(1-0.01-x)。

[0038] The phosphor provided by the present invention is Mg 2 G 8 (SiO 4 ) 6 O 2 (abbreviated as MGSO) as the original host matrix, with Bi 3+ and Eu 3+ In the present invention, 0.01 in the chemical formula represents Bi 3+ The original host matrix Mg 2 G 8 (SiO 4 ) 6 O 2 The molar ratio of Gd in the doping, x represents Eu 3+ The original host matrix Mg 2 G 8 (SiO 4 ) 6 O 2 The molar ratio of Gd doping in the original host matrix is ​​that the Gd sites in the original host matrix are doped with a certain proportion of Bi 3+ and Eu 3+ Doping substitution to form Mg 2 G z (SiO 4) 6 O 2 , wherein z=8(1-0.01-x), and the x is preferably 0.0025, 0.005, 0.01, 0.02, 0.04, 0.08 or 0.12.

[0039] In the embodiment of the present invention, the phosphor is also represented by MGSO: 1 mol% Bi 3+ ,ymol%Eu 3+ , that is, y=100x.

[0040] The apatite structure silicate phosphor provided by the present invention is Mg 2 G 8 (SiO 4 ) 6 O 2 (abbreviated as MGSO) is the matrix material, and bismuth and europium are co-doped activation ions. 2 G 8 (SiO 4 ) 6 O 2 Contains two low-symmetry cation sites, namely, the C3-symmetric 9-coordinated 4f site and the Cs-symmetric 7-coordinated 6h site. Mg and Gd atoms are distributed in the two sites in a certain proportion. The activator ions can replace the Mg or Gd sites to occupy the two sites (the activator ions in the present invention are more inclined to occupy the Gd sites). Due to the presence of Mg, the MGSO matrix has high temperature resistance and a more stable crystal structure relative to other apatite structural systems. Mg and Gd are located at the position A in the general formula and can be replaced by rare earth ions to form a luminescent center. [SiO 4 ] 4- It is an anion group, which forms a stable framework with silicon-oxygen tetrahedron, in which Si cannot be replaced by rare earth ions. The last O is an adduct anion, also known as a channel anion. There are two local symmetry C3 and Cs cationic crystal sites in apatite structure silicates, corresponding to the 9-coordinated 4f site and the 7-coordinated 6h site, respectively. Both sites can accommodate a variety of activator ions to become the luminescence center of the phosphor.

[0041] The present invention firstly combines Mg 2 G 8 (SiO 4 ) 6 O 2 Matrix and Bi 3+ 、Eu 3+ The apatite structure silicate phosphor obtained by co-doping can be effectively excited by ultraviolet light and near-ultraviolet light, has a wide absorption range, high emission intensity, good optical properties and temperature sensitivity. In the present invention, the apatite structure silicate phosphor contains Bi3+ To Eu 3+ Energy transfer, when the phosphor is excited at 315nm, Bi 3+ To Eu 3+ The energy transfer efficiency between them can reach up to 51.74%. 3+ With the increase of co-doping concentration, the luminescent color can transition from the blue light region to the red light region, thus realizing the spectrum control of the phosphor. 3+ The emission spectrum of Eu 3+ The narrowband emission is insensitive to temperature changes and is based on MGSO:Bi 3+ With Eu 3+ The temperature-dependent fluorescence intensity ratio (FIR) enables the phosphor to be highly sensitive to temperature.

[0042] The present invention provides a method for preparing the apatite structure silicate phosphor described in the above technical solution, comprising the following steps:

[0043] Mixing a magnesium source, a gadolinium source, a silicon source, a bismuth source and a europium source according to the stoichiometric ratio shown in the chemical formula of the apatite structure silicate phosphor to obtain a mixture;

[0044] The mixed material is calcined in an air atmosphere and then ground to obtain the apatite structure silicate phosphor.

[0045] In the present invention, unless otherwise specified, the raw materials involved are commercially available products well known in the art.

[0046] The present invention mixes a magnesium source, a gadolinium source, a silicon source, a bismuth source and a europium source according to the stoichiometric ratio shown in the chemical formula of the apatite structure silicate phosphor to obtain a mixture.

[0047] In the present invention, the magnesium source preferably includes magnesium oxide (MgO), magnesium nitrate (Mg(NO 3 ) 2 6H 2 O), magnesium hydroxide (Mg(OH) 2 ) and magnesium carbonate (MgCO 3 ) one or more; the gadolinium source preferably includes gadolinium oxide (Gd 2 O 3 ), one or more of gadolinium nitrate and gadolinium fluoride; the silicon source preferably includes silicon dioxide (SiO 2 ); the bismuth source preferably comprises bismuth oxide (Bi 2 O 3 ), bismuth nitrate (Bi(NO 3 ) 3 6H 2O), bismuth hydroxide (Bi(OH) 3 ) and bismuth carbonate (Bi 2 (CO 3 ) 3 ) one or more; the europium source preferably includes europium oxide (Eu 2 O 3 ), europium nitrate (Eu(NO 3 ) 3 6H 2 O), europium hydroxide (Eu(OH) 3 ) and europium carbonate (Eu 2 (CO 3 ) 3 In the present invention, the purity of the magnesium source, silicon source and gadolinium source is preferably analytically pure, and the purity of the bismuth source and europium source is preferably 99.99%.

[0048] In the present invention, the mixing method is preferably grinding, and the grinding is preferably adding grinding media, and the grinding media is preferably ethanol, and the ratio of the volume of the ethanol to the total volume of the magnesium source, gadolinium source, silicon source, bismuth source and europium source is preferably 1:1. The present invention preferably places the magnesium source, gadolinium source, silicon source, bismuth source and europium source in an agate mortar, adds grinding media, and grinds. The present invention has no special requirements for the grinding time, as long as the raw materials are mixed evenly. After the grinding, the grinding media is preferably completely evaporated.

[0049] After obtaining the mixed material, the present invention calcines the mixed material in an air atmosphere and then grinds it to obtain the apatite structure silicate phosphor.

[0050] In the present invention, the calcination temperature is preferably 1300-1500°C, specifically 1300°C, 1350°C, 1380°C, 1400°C, 1430°C, 1450°C, 1470°C, more preferably 1450°C, and the time is preferably 4-6h, more preferably 5h. The present invention preferably transfers the mixture to a corundum crucible and places it in a high-temperature tube furnace for calcination. During the calcination process, the inorganic crystalline material is finally obtained through diffusion, reaction, nucleation, growth and other processes between the raw materials.

[0051] After the calcination, the present invention preferably cools the obtained calcined material (block sample) naturally to room temperature in a high-temperature tube furnace under air atmosphere.

[0052] In the present invention, the grinding is preferably carried out in an agate mortar; the present invention has no special requirements on the particle size of the grinding, as long as it is in a uniform powder state.

[0053] The present invention synthesizes the apatite structure silicate phosphor by a high temperature solid phase method, the raw materials are easily available, the process flow is simple, the preparation cost is low, and batch production is possible; compared with sulfides, halides, and nitrides, the phosphor is energy-efficient, highly efficient, and green and environmentally friendly.

[0054] The present invention provides applications of the apatite structure silicate phosphor described in the above technical solution or the apatite structure silicate phosphor prepared by the preparation method described in the above technical solution in the fields of solid-state lighting, optical temperature sensing and temperature visualization.

[0055] The apatite structure silicate phosphor provided by the present invention has the advantages of broadband absorption and narrowband emission in the ultraviolet to visible light region, can be used to manufacture the orange-red component of ultraviolet excited white light LED, and can be combined with ultraviolet LED chips to prepare high luminous performance white light LED.

[0056] In the present invention, the optical temperature sensor preferably includes a non-contact optical temperature measuring device. The phosphor provided by the present invention is a phosphor based on the broadband and narrowband fluorescence intensity ratio in a single matrix binary co-doping system, which is based on the fluorescence intensity ratio temperature measurement of double emission peaks. This method is less dependent on measurement conditions, is not limited by the fluctuation of the intensity of the excitation light source, and the changes in luminescence intensity caused by non-temperature factors such as the number and distribution of luminescence centers, and has a small measurement error. This measurement method utilizes the different changes in the fluorescence intensity of two adjacent thermally coupled energy levels or two different luminescence centers, and uses their intensity ratio to reflect the temperature. The phosphor provided by the present invention has good application prospects in the field of non-contact optical temperature measurement.

[0057] In order to further illustrate the present invention, the apatite structure silicate phosphor provided by the present invention, its preparation method and its application in the field of fluorescent temperature sensing are described in detail below with reference to examples, but they should not be construed as limiting the protection scope of the present invention.

[0058] Example 1: Mg 2 G 8 (SiO 4 ) 6 O 2 Phosphor

[0059] Weigh 0.0806 g of MgO (analytical grade), SiO 2 (Analytically pure) 0.3605g, Gd 2 O 3(Analytically pure) 1.450g. Add the same volume of ethanol as the raw materials to the above raw materials in an agate mortar and grind for 30 minutes to fully mix the raw materials. After the raw materials are evenly mixed and the ethanol is completely evaporated, transfer the mixture into a corundum crucible, place it in a high-temperature tube furnace, and calcine it at 1350℃ for 5h in an air atmosphere; cool it naturally to room temperature in an air atmosphere in a high-temperature tube furnace, grind the calcined block sample into powder in an agate mortar to obtain the desired phosphor, and the sample emits blue light under a 365nm ultraviolet lamp.

[0060] Example 2: Mg 2 G 8(1-0.005) (SiO 4 ) 6 O 2 :0.005Bi 3+ Phosphor

[0061] Weigh 0.0806 g of MgO (analytical grade), SiO 2 (Analytically pure) 0.3605g, Bi 2 O 3 (99.99%) 0.0093 g, Gd 2 O 3 (Analytically pure) 1.4428g. Add the same volume of ethanol as the raw materials to the above raw materials in an agate mortar and grind for 30 minutes to fully mix the raw materials. After the raw materials are evenly mixed and the ethanol is completely evaporated, transfer the mixture into a corundum crucible, place it in a high-temperature tube furnace, and calcine it at 1350℃ for 5h in an air atmosphere; cool it naturally to room temperature in an air atmosphere in a high-temperature tube furnace, grind the calcined block sample into powder in an agate mortar to obtain the desired phosphor, and the sample emits blue light under a 365nm ultraviolet lamp.

[0062] Example 3: Mg 2 G 8(1-0.01) (SiO 4 ) 6 O 2 :0.01Bi 3+ Phosphor

[0063] Weigh 0.0806 g of MgO (analytical grade), SiO 2 (Analytically pure) 0.3605g, Bi 2 O 3 (99.99%) 0.0186 g, Gd 2 O 3(Analytically pure) 1.4355g. Add the same volume of ethanol as the raw materials to the above raw materials in an agate mortar and grind for 30 minutes to fully mix the raw materials. After the raw materials are evenly mixed and the ethanol is completely evaporated, transfer the mixture into a corundum crucible, place it in a high-temperature tube furnace, and calcine it at 1350℃ for 5h in an air atmosphere; cool it naturally to room temperature in an air atmosphere in a high-temperature tube furnace, grind the calcined block sample into powder in an agate mortar to obtain the desired phosphor, and the sample emits blue light under a 365nm ultraviolet lamp.

[0064] Example 4: Mg 2 G 8(1-0.02) (SiO 4 ) 6 O 2 :0.02Bi 3+ Phosphor

[0065] Weigh 0.0806 g of MgO (analytical grade), SiO 2 (Analytically pure) 0.3605g, Bi 2 O 3 (99.99%) 0.0373 g, Gd 2 O 3 (Analytically pure) 1.421g. Add the same volume of ethanol as the raw materials to the above raw materials in an agate mortar and grind for 30 minutes to fully mix the raw materials. After the raw materials are evenly mixed and the ethanol is completely evaporated, transfer the mixture into a corundum crucible, place it in a high-temperature tube furnace, and calcine it at 1350℃ for 5h in an air atmosphere; cool it naturally to room temperature in an air atmosphere in a high-temperature tube furnace, and grind the calcined block sample into powder in an agate mortar to obtain the desired phosphor. The sample emits blue light under a 365nm ultraviolet lamp.

[0066] Example 5: Mg 2 G 8(1-0.03) (SiO 4 ) 6 O 2 :0.03Bi 3+ Phosphor

[0067] Weigh 0.0806 g of MgO (analytical grade), SiO 2 (Analytically pure) 0.3605g, Bi 2 O 3 (99.99%) 0.0559 g, Gd 2 O 3(Analytically pure) 1.4065g. Add the same volume of ethanol as the raw materials to the above raw materials in an agate mortar and grind for 30 minutes to fully mix the raw materials. After the raw materials are evenly mixed and the ethanol is completely evaporated, transfer the mixture into a corundum crucible, place it in a high-temperature tube furnace, and calcine it at 1350℃ for 5h in an air atmosphere; cool it to room temperature in an air atmosphere in a high-temperature tube furnace, grind the calcined block sample into powder in an agate mortar to obtain the desired phosphor, and the sample emits blue light under a 365nm ultraviolet lamp.

[0068] Example 6: Mg 2 G 8(1-0.04) (SiO 4 ) 6 O 2 :0.04Bi 3+ Phosphor

[0069] Weigh 0.0806 g of MgO (analytical grade), SiO 2 (Analytically pure) 0.3605g, Bi 2 O 3 (99.99%) 0.0745 g, Gd 2 O 3 (Analytically pure) 1.392g. Add the same volume of ethanol as the raw materials to the above raw materials in an agate mortar and grind for 30 minutes to fully mix the raw materials. After the raw materials are evenly mixed and the ethanol is completely evaporated, transfer the mixture into a corundum crucible, place it in a high-temperature tube furnace, and calcine it at 1350℃ for 5h in an air atmosphere; cool it naturally to room temperature in an air atmosphere in a high-temperature tube furnace, grind the calcined block sample into powder in an agate mortar to obtain the desired phosphor, and the sample emits blue light under a 365nm ultraviolet lamp.

[0070] Example 7: Mg 2 G 8(1-0.05) (SiO 4 ) 6 O 2 :0.05Bi 3+ Phosphor

[0071] Weigh 0.0806 g of MgO (analytical grade), SiO 2 (Analytically pure) 0.3605g, Bi 2 O 3 (99.99%) 0.0932 g, Gd 2 O 3(Analytically pure) 1.3775g. Add the same volume of ethanol as the raw materials to the above raw materials in an agate mortar and grind for 30 minutes to fully mix the raw materials. After the raw materials are evenly mixed and the ethanol is completely evaporated, transfer the mixture into a corundum crucible, place it in a high-temperature tube furnace, and calcine it at 1350℃ for 5h in an air atmosphere; cool it naturally to room temperature in an air atmosphere in a high-temperature tube furnace, grind the calcined block sample into powder in an agate mortar to obtain the desired phosphor, and the sample emits blue light under a 365nm ultraviolet lamp.

[0072] Figure 1 This is a photo of the phosphor obtained in Examples 2 to 7 under a 365nm UV lamp. Figure 1 From left to right in the figure are the corresponding embodiments 2 (Mg 2 G 8(1-0.005) (SiO 4 ) 6 O 2 :0.005Bi 3+ )、Example 3 (Mg 2 G 8(1-0.01) (SiO 4 ) 6 O 2 :0.01Bi 3 + )、Example 4 (Mg 2 G 8(1-0.02) (SiO 4 ) 6 O 2 :0.02Bi 3+ ), Example 5 (Mg 2 G 8(1-0.03) (SiO 4 ) 6 O 2 :0.03Bi 3+ ), Example 6 (Mg 2(1-0.04) G 8 (SiO 4 ) 6 O 2 :0.04Bi 3+ )、Example 7 (Mg 2 G 8(1-0.05) (SiO 4 ) 6 O 2 :0.05Bi 3+ ) of phosphor, of which 0.01Bi 3+ It is the optimal dosage, and the luminous intensity of the phosphor is the highest at this time.

[0073] Example 8: Mg 2 G 8(1-0.01-0.0025) (SiO4 ) 6 O 2 :0.01Bi 3+ ,0.0025Eu 3+ Phosphor

[0074] Weigh 0.0806 g of MgO (analytical grade), SiO 2 (Analytically pure) 0.3605g, Bi 2 O 3 (99.99%) 0.0186g, Eu 2 O 3 (99.99%)0.0035g, Gd 2 O 3 (Analytically pure) 1.4319g. Add the same volume of ethanol as the raw materials to the above raw materials in an agate mortar and grind for 40 minutes to fully mix the raw materials. After the raw materials are evenly mixed and the ethanol is completely evaporated, transfer the mixture into a corundum crucible, place it in a high-temperature tube furnace, and calcine it at 1450℃ for 5h in an air atmosphere; cool it to room temperature in an air atmosphere in a high-temperature tube furnace, and grind the calcined block sample into powder in an agate mortar to obtain the desired phosphor. The sample emits blue light under a 365nm ultraviolet lamp.

[0075] Example 9: Mg 2 G 8(1-0.01-0.005) (SiO 4 ) 6 O 2 :0.01Bi 3+ ,0.005Eu 3+ Phosphor

[0076] Weigh 0.0806 g of MgO (analytical grade), SiO 2 (Analytically pure) 0.3605g, Bi 2 O 3 (99.99%) 0.0186g, Eu 2 O 3 (99.99%)0.0070g, Gd 2 O 3 (Analytically pure) 1.4283g. Add the same volume of ethanol as the raw materials to the above raw materials in an agate mortar and grind for 40 minutes to fully mix the raw materials. After the raw materials are evenly mixed and the ethanol is completely evaporated, transfer the mixture into a corundum crucible, place it in a high-temperature tube furnace, and calcine it at 1450℃ for 5h in an air atmosphere; cool it naturally to room temperature in an air atmosphere in a high-temperature tube furnace, grind the calcined block sample into powder in an agate mortar to obtain the desired phosphor, and the sample emits blue light under a 365nm ultraviolet lamp.

[0077] Example 10: Mg2 G 8(1-0.01-0.01) (SiO 4 ) 6 O 2 :0.01Bi 3+ ,0.01Eu 3+ Phosphor

[0078] Weigh 0.0806 g of MgO (analytical grade), SiO 2 (Analytically pure) 0.3605g, Bi 2 O 3 (99.99%) 0.0186g, Eu 2 O 3 (99.99%) 0.0141 g, Gd 2 O 3 (Analytically pure) 1.421g. Add the same volume of ethanol as the raw materials to the above raw materials in an agate mortar and grind for 40 minutes to fully mix the raw materials. After the raw materials are evenly mixed and the ethanol is completely evaporated, transfer the mixture into a corundum crucible, place it in a high-temperature tube furnace, and calcine it at 1450℃ for 5h in an air atmosphere; cool it naturally to room temperature in an air atmosphere in a high-temperature tube furnace, grind the calcined block sample into powder in an agate mortar to obtain the desired phosphor, and the sample emits bluish-white light under a 365nm ultraviolet lamp.

[0079] Example 11: Mg 2 G 8(1-0.01-0.02) (SiO 4 ) 6 O 2 :0.01Bi 3+ ,0.02Eu 3+ Phosphor

[0080] Weigh 0.0806 g of MgO (analytical grade), SiO 2 (Analytically pure) 0.3605g, Bi 2 O 3 (99.99%) 0.0186g, Eu 2 O 3 (99.99%) 0.0281 g, Gd 2 O 3 (Analytically pure) 1.4065g. Add the same volume of ethanol as the raw materials to the above raw materials in an agate mortar and grind for 40 minutes to fully mix the raw materials. After the raw materials are evenly mixed and the ethanol is completely evaporated, transfer the mixture into a corundum crucible, place it in a high-temperature tube furnace, and calcine it at 1450℃ for 5h in an air atmosphere; cool it naturally to room temperature in an air atmosphere in a high-temperature tube furnace, grind the calcined block sample into powder in an agate mortar to obtain the desired phosphor, and the sample emits yellow-orange light under a 365nm ultraviolet lamp.

[0081] Example 12: Mg 2 G 8(1-0.01-0.04) (SiO 4 ) 6 O 2 :0.01Bi 3+ ,0.04Eu 3+ Phosphor

[0082] Weigh 0.0806 g of MgO (analytical grade), SiO 2 (Analytically pure) 0.3605g, Bi 2 O 3 (99.99%) 0.0186g, Eu 2 O 3 (99.99%) 0.0563 g, Gd 2 O 3 (Analytically pure) 1.3775g. Add the same volume of ethanol as the raw materials to the above raw materials in an agate mortar and grind for 40 minutes to fully mix the raw materials. After the raw materials are evenly mixed and the ethanol is completely evaporated, transfer the mixture into a corundum crucible, place it in a high-temperature tube furnace, and calcine it at 1450℃ for 5h in an air atmosphere; cool it naturally to room temperature in an air atmosphere in a high-temperature tube furnace, grind the calcined block sample into powder in an agate mortar to obtain the desired phosphor, and the sample emits yellow-orange light under a 365nm ultraviolet lamp.

[0083] Example 13: Mg 2 G 8(1-0.01-0.08) (SiO 4 ) 6 O 2 :0.01Bi 3+ , 0.08Eu 3+ Phosphor

[0084] Weigh 0.0806 g of MgO (analytical grade), SiO 2 (Analytically pure) 0.3605g, Bi 2 O 3 (99.99%) 0.0186g, Eu 2 O 3 (99.99%) 0.1126 g, Gd 2 O 3(Analytically pure) 1.3195g. Add the same volume of ethanol as the raw materials to the above raw materials in an agate mortar and grind for 40 minutes to fully mix the raw materials. After the raw materials are evenly mixed and the ethanol is completely evaporated, transfer the mixture into a corundum crucible, place it in a high-temperature tube furnace, and calcine it at 1450℃ for 5h in an air atmosphere; cool it naturally to room temperature in an air atmosphere in a high-temperature tube furnace, grind the calcined block sample into powder in an agate mortar to obtain the desired phosphor, and the sample emits orange light under a 365nm ultraviolet lamp.

[0085] Example 14: Mg 2 G 8(1-0.01-0.12) (SiO 4 ) 6 O 2 :0.01Bi 3+ , 0.12Eu 3+ Phosphor

[0086] Weigh 0.0806 g of MgO (analytical grade), SiO 2 (Analytically pure) 0.3605g, Bi 2 O 3 (99.99%) 0.0186g, Eu 2 O 3 (99.99%) 0.1689 g, Gd 2 O 3 (Analytically pure) 1.2615g. Add the same volume of ethanol as the raw materials to the above raw materials in an agate mortar and grind for 40 minutes to fully mix the raw materials. After the raw materials are evenly mixed and the ethanol is completely evaporated, transfer the mixture into a corundum crucible, place it in a high-temperature tube furnace, and calcine it at 1450℃ for 5h in an air atmosphere; cool it naturally to room temperature in an air atmosphere in a high-temperature tube furnace, grind the calcined block sample into powder in an agate mortar to obtain the desired phosphor, and the sample emits orange-red light under a 365nm ultraviolet lamp.

[0087] Figure 2 This is a photo of the luminescence of the phosphors obtained in Examples 8 to 14 under a 365nm UV lamp. Figure 2 From left to right in the figure are the corresponding embodiments 8 (Mg 2 G 8(1-0.01-0.0025) (SiO 4 ) 6 O 2 :0.01Bi 3+ ,0.0025Eu 3+ ), Example 9 (Mg 2 G 8(1-0.01-0.005) (SiO 4 ) 6 O 2 :0.01Bi3+ ,0.005Eu 3+ ), Example 10 (Mg 2 G 8(1-0.01-0.01) (SiO 4 ) 6 O 2 :0.01Bi 3+ ,0.01Eu 3+ ), Example 11 (Mg 2 G 8(1-0.01-0.02) (SiO 4 ) 6 O 2 :0.01Bi 3+ ,0.02Eu 3+ ), Example 12 (Mg 2 G 8(1-0.01-0.04) (SiO 4 ) 6 O 2 :0.01Bi 3+ ,0.04Eu 3+ ), Example 13 (Mg 2 G 8(1-0.01-0.08) (SiO 4 ) 6 O 2 :0.01Bi 3+ 0.08Eu 3+ ), Example 14 (Mg 2 G 8(1-0.01-0.12) (SiO 4 ) 6 O 2 :0.01Bi 3+ ,0.12Eu 3+ ) of phosphor.

[0088] Figure 3 The PL spectra of the phosphors obtained in Examples 8 to 14 under 315 nm excitation are shown in Figure 1. 3+ Doping concentration, find the maximum emission intensity, determine the best doping Eu 3+ The molar concentration of 0.08Eu 3+ is the optimal doping concentration, at which the emission intensity is maximum.

[0089] The present invention is based on Bi 3+ With Eu 3+ The energy transfer mechanism between them has resulted in a series of MGSO:Bi with tunable emission colors. 3+ ,Eu 3+ Phosphor. In order to more intuitively understand the effect of luminescent color on Eu 3+ The concentration dependence of MGSO:1mol%Bi3+ ,y mol%Eu 3+ The PL spectrum of the sample (y = 0.25 ~ 12.00) was converted into chromaticity coordinates for observation. The color points of the above samples and the corresponding photos under 365nm UV light were plotted on the CIE chromaticity coordinates. The results are as follows Figure 4 As shown, Figure 4 (a) is a CIE chromaticity coordinate diagram, and the inset is a photo of the phosphor under a 365nm UV lamp (the corresponding y from left to right is 0.25, 0.5, 1, 2, 4, 8, 12). Figure 4 (b) is the chromaticity coordinate value of the phosphor at room temperature when y=0.25~12. It can be clearly seen that as Eu 3+ The continuous increase in doping concentration gradually achieves the tuning of the phosphor from blue light to red light.

[0090] Figure 5 Mg prepared in Example 3 2 G 8(1-0.01) (SiO 4 ) 6 O 2 :0.01Bi 3+ Phosphor (MGSO: 1mol%Bi 3+ ), Mg prepared in Example 10 2 G 8(1-0.01-0.01) (SiO 4 ) 6 O 2 :0.01Bi 3+ ,0.01Eu 3+ Phosphor (MGSO: 1mol%Bi 3+ ,1mol%Eu 3+ ) and Mg 2 G 8 (SiO 4 ) 6 O 2 XRD diffraction patterns of the host matrix (MGSO Host). The diffraction patterns obtained in Example 3 and Example 10 are similar to those of Mg 2 G 8 (SiO 4)6 O 2 The ICSD card is consistent with that of the 3+ / Eu 3+ After the ions enter the lattice, the sample still maintains the pure phase of MGSO. For further analysis, the diffraction patterns of the above three samples were refined by Rietveld. The original model used for Rietveld refinement analysis was also Mg 2 G 8 (SiO4 ) 6 O 2 , the results are as follows Figure 6 As shown in Figure 2, the Rietveld refinement results of the diffraction pattern show that the crystal structure data is reliable, which further illustrates that the obtained phosphor sample is still pure phase under the doping of the activator. 2 G 8(1-0.01) (SiO 4 ) 6 O 2 :0.01Bi 3+ Phosphor (MGSO: 1mol%Bi 3+ ), Mg prepared in Example 10 2 G 8(1-0.01-0.01) (SiO 4 ) 6 O 2 :0.01Bi 3+ ,0.01Eu 3+ Phosphor (MGSO: 1mol%Bi 3+ ,1mol%Eu 3+ ) and Mg 2 G 8 (SiO 4 ) 6 O 2 The refinement parameters of the main matrix (MGSO) are shown in Table 1.

[0091] Table 1 MGSO: 1 mol% Bi 3+ MGSO:1mol%Bi 3+ ,1mol%Eu 3+ And the refined parameters of MGSO

[0092]

[0093] Crystal structure model of MGSO ( Figure 8 As shown in Figure 2, MGSO crystals are composed of three types of polyhedrons, namely, 9-coordinated tetradecahedron, 7-coordinated decahedron, and 4-coordinated Si-O tetrahedron. However, since Si-O tetrahedron will not be replaced by activator ion doping, it will not be discussed. The central atom of the tetradecahedron and decahedron is Mg 2+ or Gd 3+ Atoms, both of which are distributed in a certain proportion, can accommodate the activator ion. The tetradecahedron consists of a cation (Mg 2+ or Gd 3+ ) and nine surrounding oxygen atoms. The cation is located at the 4f site and has C3 symmetry. The decahedron consists of a cation (Mg 2+ or Gd 3+) and seven surrounding oxygen atoms, the cation is located at the 6h site and has Cs symmetry. Rietveld refinement results show that Bi 3+ and Eu 3 + It is more inclined to occupy the Gd site to form a luminescent center.

[0094] Mg prepared in Example 10 2 G 8(1-0.01-0.01) (SiO 4 ) 6 O 2 :0.01Bi 3+ ,0.01Eu 3+ Phosphor (MGSO: 1mol%Bi 3+ ,1mol%Eu 3+ ) were characterized by SEM and EDS. The results are shown in Figure 7 As shown. By MGSO:Bi 3+ ,Eu 3+ The SEM image of the sample reflects the microscopic morphology of the phosphor, and the uniformity of element distribution is analyzed by EDS element mapping technology. The results show that Mg, Gd, Si, O, Bi and Eu elements are evenly distributed in the matrix, proving that the reactants are the desired substances.

[0095] From the measured emission spectrum, we can see that Bi 3+ and Eu 3+ The emission bands of the prepared MGSO:Bi 3+ ,Eu 3+ In order to explore the potential application of the prepared samples in optical temperature measurement, MGSO:1mol%Bi 3+ ,1mol%Eu 3+ PL spectra of samples at different temperatures. MGSO:1mol%Bi in the range of 298~498K 3+ ,1mol%Eu 3+ The temperature-dependent PL spectrum (i.e., variable temperature spectrum) is as follows: Fig. 9 As shown ( Fig. 9 The characteristic peak of Bi is shown in the lower middle area (350-525 nm). During the heating process, the intensity change of the PL spectrum of the sample as a whole shows a similar trend, that is, Bi 3+ and Eu 3+ The corresponding PL spectrum intensity gradually decreases with increasing temperature, which is a common phenomenon caused by the thermal quenching effect. Fig.10 The integrated intensity histogram shows that in MGSO:1mol%Bi 3+,1mol%Eu 3+ Medium, Bi 3+ The fluorescence intensity of Eu 3+ To Bi 3+ The FIR value of ions is strongly dependent on temperature. Fig.11 The temperature-dependent FIR fitting curve shows that different data values ​​can be used to measure different temperatures.

[0096] Based on the above characteristics, the absolute sensitivity (S a ) and relative sensitivity (S r ), Fig.12 MGSO:1mol%Bi 3 + ,1mol%Eu 3+ The change law of Sa and Sr values ​​of phosphor with temperature shows that the maximum absolute sensitivity S a =0.0047K -1 , maximum relative sensitivity S r =0.92%K -1 (498K). Prepare MGSO:1mol%Bi 3+ ,1mol%Eu 3+ The Sa and Sr values ​​of the phosphors were compared with those of some recently published temperature-sensitive phosphors (as shown in Table 2. 2 G 8 (SiO 4 ) 6 O 2 :Bi 3+ ,Eu 3+ MGSO: 1 mol% Bi 3+ ,1mol%Eu 3+ Phosphor, SrY 2 O 4 :Bi 3+ ,Eu 3+ and SrLu 2 O 4 :Bi 3+ ,Eu 3+ is a recently reported phosphor), MGSO: 1 mol% Bi 3+ ,1mol%Eu 3+ The Sr value of the phosphor is higher than the results reported in the literature. In the range of 298-498K, MGSO:1mol%Bi 3+ ,1mol%Eu 3+ The PL spectrum chromaticity coordinates of the phosphor sample are as follows: Fig.14 As shown in Figure 2, the color changes with temperature in a regular trend. Fig.13As shown in Figure 2, the FIR curve of the sample is almost completely reversible during the heating (298→498K) and cooling (498→298K) processes. 3+ ,1mol%Eu 3+ The phosphor has excellent temperature sensitivity and FIR recovery during heating and cooling processes, which shows that it has potential application value in the field of temperature sensing.

[0097] Table 2 Comparison of optical parameters of temperature-sensitive phosphors

[0098]

[0099]

[0100] Embodiment 15

[0101] MGSO:0.01Bi at different preparation temperatures 3+ ,0.01Eu 3+ Research on phosphors

[0102] The calcination temperatures in Example 10 were changed to 1250°C, 1300°C, 1350°C, 1380°C, 1400°C, 1430°C and 1470°C respectively, and the rest were the same as Example 10.

[0103] The phosphor was obtained under the calcination temperature of 1250℃, but the pure phase sample could not be synthesized.

[0104] The phosphor was obtained under the calcination temperature of 1300℃, but the pure phase sample could not be synthesized.

[0105] The phosphor was obtained under the condition of calcination temperature of 1350°C and a pure phase sample was synthesized, but the luminescence intensity of the sample was low under 365nm ultraviolet lamp.

[0106] The phosphor was obtained under the condition of calcination temperature of 1380°C. The sample was pure phase, but the luminescence intensity of the sample was low under 365nm ultraviolet lamp.

[0107] The phosphor was obtained under the condition of calcination temperature of 1400°C. The sample was pure phase and the luminous intensity of the sample was moderate under 365nm ultraviolet lamp.

[0108] The phosphor was obtained under the condition of calcination temperature of 1430°C. The sample was pure phase and the luminous intensity of the sample was moderate under 365nm ultraviolet lamp.

[0109] When the calcination temperature was 1470°C, the phosphor was obtained, but the sample melted and had no luminous effect.

[0110] In Example 10, the phosphor was obtained under a calcination temperature of 1450°C, and a pure phase was synthesized. The luminous intensity of the sample was optimal under a 365nm ultraviolet lamp.

[0111] The present invention synthesizes a series of MGSO:Bi by high temperature solid phase method 3+ and MGSO:Bi 3+ ,Eu 3+ Phosphor. The morphology, structure, luminescence performance and temperature sensitivity of the prepared phosphor were systematically characterized, and the MGSO:Bi 3+ ,Eu 3+ Zhongbi 3+ →Eu 3+ The energy transfer mechanism is achieved by controlling the Eu 3+ The doping concentration achieves the tuning of the phosphor from blue light to red light. 3+ After that, the color coordinate position and correlated color temperature (CCT) of the phosphor changed. In the temperature spectrum test, it was found that MGSO:Bi 3+ The emission spectrum of Eu 3+ The narrowband emission of MGSO:Bi is not sensitive to temperature changes. 3+ ,Eu 3+ The FIR changes with temperature, and the phosphor can be used for non-contact optical temperature measurement. 3+ ,Eu 3+ Phosphors have potential applications in solid-state lighting and optical temperature measurement.

[0112] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be regarded as the protection scope of the present invention.

Claims

1. An apatite structure silicate phosphor, characterized in that: The chemical formula is: Mg2Gd z (SiO4)6O2:0.01Bi 3+ ,xEu 3+ ; where 0 <x≤0.12,z=8(1-0.01-x)。 2. The apatite structure silicate phosphor according to claim 1, characterized in that: The x is 0.0025, 0.005, 0.01, 0.02, 0.04, 0.08 or 0.

12.

3. The method for preparing the apatite structure silicate phosphor according to claim 1 or 2, characterized in that: The following steps are involved: Mixing a magnesium source, a gadolinium source, a silicon source, a bismuth source and a europium source according to the stoichiometric ratio shown in the chemical formula of the apatite structure silicate phosphor to obtain a mixture; The mixed material is calcined in an air atmosphere and then ground to obtain the apatite structure silicate phosphor.

4. The preparation method according to claim 3, characterized in that: The magnesium source includes one or more of magnesium oxide, magnesium nitrate, magnesium hydroxide and magnesium carbonate; the gadolinium source includes one or more of gadolinium oxide, gadolinium nitrate and gadolinium fluoride; the silicon source includes silicon dioxide; the bismuth source includes one or more of bismuth oxide, bismuth nitrate, bismuth hydroxide and bismuth carbonate; the europium source includes one or more of europium oxide, europium nitrate, europium hydroxide and europium carbonate.

5. The preparation method according to claim 3 or 4, characterized in that: The mixing method is grinding.

6. The preparation method according to claim 5, characterized in that: The grinding process involves adding a grinding medium, wherein the grinding medium is ethanol.

7. The preparation method according to claim 3, characterized in that: The calcination temperature is 1300-1500° C. and the calcination time is 4-6 hours.

8. The preparation method according to claim 7, characterized in that: The calcination temperature is 1450° C. and the calcination time is 5 hours.

9. Application of the apatite structure silicate phosphor according to claim 1 or 2 or the apatite structure silicate phosphor prepared by the preparation method according to any one of claims 3 to 8 in the fields of solid-state lighting, optical temperature sensing and temperature visualization.

10. The use according to claim 9, characterized in that: The solid-state lighting includes a white light LED, and the optical temperature sensor includes a non-contact optical temperature measurement device.